Next-Generation 3D Vision and Robotic Integration Technologies for Commercial Vehicle Manufacturing - Md Nazmul Islam; Ren Aihua; Muhammad Isyaku; Benfor Nana Boa; Shahin Alam (Control Systems and Optimization Letters, 2026)
This research project explores the development of 3D machine vision and robot integration technology tailored for commercial vehicle manufacturing and testing. As the industry increasingly demands higher efficiency and quality, the integration of advanced machine vision systems with robotic automation presents a transformative solution. Advanced robotics technologies involve the latest advances in robotics, including integrating sophisticated control systems, sensors, data fusion techniques, and machine learning algorithms. These innovations enable robots to adapt better and interact with their environment, ultimately increasing their accuracy. The main focus of this study is to cover the most common industrial robotic machining processes and to identify how specific advanced technologies can improve their performance. In most of the studied literature, the primary research objective across all operations is to enhance the stiffness of the robotic arm’s structure. This study investigates the implementation of 3D machine vision for precise component inspection, guided assembly, and real-time process adaptation. Key challenges, including high initial costs and complexity of integration, are addressed alongside potential benefits such as improved product quality and reduced operational costs. By leveraging cutting-edge technologies, this research aims to enhance manufacturing processes, ultimately contributing to the advancement of intelligent manufacturing in the commercial vehicle sector. The findings will provide valuable insights for manufacturers seeking to optimize their production capabilities and maintain competitiveness in a rapidly evolving market.